2007
DOI: 10.5840/beq20071745
|View full text |Cite
|
Sign up to set email alerts
|

Sweatshops, Choice, and Exploitation

Abstract: ABSTRACT:This paper argues that sweatshop workers’ choices to accept the conditions of their employment are morally significant, both as an exercise of their autonomy and as an expression of their preferences. This fact establishes a moral claim against interference in the conditions of sweatshop labor by third parties such as governments or consumer boycott groups. It should also lead us to doubt those who call for MNEs to voluntarily improve working conditions, at least when their arguments are based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(102 citation statements)
references
References 29 publications
0
101
0
1
Order By: Relevance
“…3 All I need to establish for my present purposes is that charging a price to which a buyer freely agrees may still be ethically objectionable. As I think that the brief discussion in the text is sufficient for this limited purpose, I do not pause to discuss the existing, and very interesting, literature on exploitation: Arnold (2003), Mayer (2007), Meyers (2004), Sample (2003), Wertheimer (1996), and Zwolinski (2007Zwolinski ( , 2008.…”
Section: Resultsmentioning
confidence: 97%
“…3 All I need to establish for my present purposes is that charging a price to which a buyer freely agrees may still be ethically objectionable. As I think that the brief discussion in the text is sufficient for this limited purpose, I do not pause to discuss the existing, and very interesting, literature on exploitation: Arnold (2003), Mayer (2007), Meyers (2004), Sample (2003), Wertheimer (1996), and Zwolinski (2007Zwolinski ( , 2008.…”
Section: Resultsmentioning
confidence: 97%
“…As a consequence, there is some evidence that suppliers' compliance with codes of conduct imposed by multinational enterprises is partly limited (EngelsZandén, 2007;Locke et al, 2007;Yu, 2008). Moreover, there has been some debate whether or not such imposed standards are indeed the best way to support economic improvements in less developed countries (e.g., Zwolinski, 2007). Nonetheless, many multinationals have hardly a choice to omit such standards.…”
Section: Global Codes Of Ethicsmentioning
confidence: 93%
“…Arnold and Hartman, 2006), Zwolinski (2007) has demonstrated that the adoption of moral principles that would render it morally illegitimate to pay people less than a 'living wage', or that would render it morally illegitimate to employ people in 'sweatshop' conditions, would likely result in profit motivated companies refraining from investing in those places that arguably need it most.…”
Section: Statesmentioning
confidence: 97%